Vertebral fractures: Prevalence, risk factors, and health-related quality of life. A cross-sectional study The Tromsø study 2007/2008 - Waterloo, Svanhild Haugnes (UiT-Norges arktiske universitet, 2013)
Summary Background: Osteoporotic fractures constitute a major health burden in western societies. Forearm, vertebral-, and hip fractures are the most common types. Norway has the highest reported prevalence of forearm- and hip fractures. Little data has been available concerning vertebral fractures, although these, together with the hip fractures, are associated with increased morbidity and mortality. The aim of this thesis was to describe the prevalence of vertebral fractures in a general population, and to study important, associated risk factors and health-related quality of life. Material and method: Information on prevalent vertebral fractures was ascertained by a vertebral fracture assessment (VFA) method (dual-energy X-ray absorptiometry (DXA), GE Lunar Prodigy) in 2887 women and men, mean age 65.4, in the population-based Tromsø Study 2007-08. Bone mineral density (BMD; g/cm²) was measured at the hip by DXA. Demographic factors, lifestyle, and health-related quality of life information was collected by questionnaires. To explore associations, we used logistic and multiple regression analyses. Results: Vertebral fractures were found with an equal distribution of 12 % in women and 14 % in men, most common between 1st lumbar and 6th thoracic vertebra. In both sexes, the number of vertebral fractures increased with increasing age and declining BMD. Population attributable risk fraction for these two factors was 46% in women and 33% in men. Self-reported health-related quality of life was reduced in women with vertebral fractures compared to those without. In men there was no difference, indicating that prevalent vertebral fractures does not necessarily have an impact on men’s self-perceived health. Conclusions: The prevalence of vertebral fractures in this population was lower than expected. Men had similar fracture rates as women, but less bothered. These findings deserve a longitudinal follow-up.